Can methotrexate be used as a steroid sparing agent in the treatment of polymyalgia rheumatica and giant cell arteritis? - van der Veen, M J (1996)
OBJECTIVE: To investigate whether methotrexate (MTX) has a steroid sparing effect in the treatment of polymyalgia rheumatica (PMR) and giant cell arteritis (GCA). METHODS: We carried out a randomised double blind, placebo controlled study in 40 patients with PMR, six of whom also had clinical symptoms of GCA. A temporal artery biopsy specimen was available from 37 patients; GCA was found in six of the specimens. Among the six patients with clinical signs of GCA, three had a positive biopsy specimen. All patients were started on prednisone 20 mg/day, irrespective of clinical signs and biopsy result, supplemented with a weekly, blinded capsule containing either MTX 7.5 mg or placebo. The prednisone dose was decreased as soon as clinical symptoms disappeared and erythrocyte sedimentation rate, C reactive protein level, or both, had normalised. RESULTS: Twenty one patients were followed for two years, or at least one year after discontinuing medication. No differences were found between the MTX group and the placebo group concerning time to achieve remission, duration of remission, number of relapses, or cumulative prednisone doses. After 21 weeks the mean daily prednisone dose was reduced by 50%. Forty percent of all patients were able to discontinue prednisone within two years. Median duration of steroid treatment was 47.5 weeks (range 3-104). No serious complications from GCA were encountered. CONCLUSIONS: With a (rapid) steroid tapering regimen, it was possible to reduce the mean daily prednisone dose by 50% in 21 weeks and to cease prednisone in 40% of the patients within two years. With this regimen, no steroid sparing effect of MTX in a dosage of 7.5 mg/week was found.